ATMPH 2020
DOI: 10.36295/asro.2020.231718
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Fantasy Sports on Indian Sports Market

Abstract: Background:Fantasy sports came into existence in early 2000 in the US and Canada; however, its introduction to the Indian market was in 2008 during the first season of the Indian Premier League (IPL). Fantasy sports rapidly captured the Indian market by attracting consumers and affecting the different sectors of the market and changed the psychology of the people towards sports. The sudden growth of sensation in viewers for fantasy sports increased the interest of people in watching different sports what resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Bhattacharya et al (2020) reported money and price as significant drivers for engagement in fantasy sports in only 11.8% of their participants. 15 A systematic review of motivations for fantasy sports participation did not list rewards and prizes as some of the strongest motivations for participation in season-long fantasy sports leagues. 19 In addition to the monetary purposes, previous research has listed entertainment, competition, surveillance, arousal, entertainment, escape, social interaction, friends, sense of community, utilization of knowledge in sports, love of sports, vicarious involvement as a manager/general manager, and achievement/self-esteem as the motives for participation in fantasy sports.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Bhattacharya et al (2020) reported money and price as significant drivers for engagement in fantasy sports in only 11.8% of their participants. 15 A systematic review of motivations for fantasy sports participation did not list rewards and prizes as some of the strongest motivations for participation in season-long fantasy sports leagues. 19 In addition to the monetary purposes, previous research has listed entertainment, competition, surveillance, arousal, entertainment, escape, social interaction, friends, sense of community, utilization of knowledge in sports, love of sports, vicarious involvement as a manager/general manager, and achievement/self-esteem as the motives for participation in fantasy sports.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21][22] Previous studies have revealed a love for sports, game interests, a feeling of control, and entertainment and fun-seeking to be motives for engagement in fantasy sports. 15,18 Gambling motives among fantasy sports participants remain largely unexplored. 23 The current study examined the various motives for engagement with fantasy sports.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations